Association between heel-height and low back pain in sales promotion girls - Andhika Rezky Bahrizal; Meiyanti Meiyanti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background: The Prevalence of LBP in Indonesia continues to increase, while the exact cause cannot be identified. The facts show that most of LBP is caused by occupational health problems rather than organic diseases, which one of them is the habit of wearing high-heeled shoes. Besides having an aesthetic function, high-heeled shoes also give negative effects on health. Objective: To evaluate the association between the usage and duration of high heels with LBP, as well as evaluating disability due to LBP in female salespersonMethods: The study used analytic observational study with cross-sectional design that includes 123 sales promotion girls in one of department stores, Cengkareng, West Jakarta which was carried out from November to December 2015. The data was collected through the interview which includes characteristics of the subjects, complaint history of low back pain (LBP), measurement of heel heights, and anthropometry data. The intensity of pain is assessed by Visual Analogue Scale, whilst the degree of disability is assessed by using Oswestry Low Back Pain Disability Questionnaire. Data analysis is performed by using Fisher’s test with a significance level p<0.05 software SPSS for Windows version 21.Results: The majority of 20 to 25-year-old sales promotion girls with a normal nutritional status wear 5-7 cm-high-heeled shoes for more than one year. About 68% of them complain of low back pain (LBP), where 11% of subjects were obtained with suspected disability due to LBP complaint. The heel heights is not correlated with LPB complaints, but the working period of sales promotion girls is (p=0.000).Conclusion: There is no correlation between high heel shoes with low back pain. There is a relationship between the working period with low back pain.